Exploring social network analysis techniques on decision support - Freire, Manuela (2015)
Managers are increasingly concerned in making timely and correct decisions, using adaptable decision structures, processes and mechanisms. For this purpose, they resort to web discourse capture and analysis to obtain opinions that express different points of view, regarding organizational decision-making. Since communication and interaction among groups are very important in group decision, the exchanged and shared contents, as well as a social network analysis (SNA), can play an important role in this process. Understanding the interactions within a social network and how they can support decision-making is an important issue, representing the main motivation for this work. For the study presented in this paper, to understand how organizations can strategically use online communication as a decision support tool, we chose to use Facebook, where social actors gather around the same focus of interest or affinity (friends, co-workers, etc.) and, additionally, it is possible to create discussion groups for defining a problem, limit group members and context argument. In addition, we chose an ego-centric analysis focused on a single actor, instead of the network as a whole, to get a good picture of the “local” or his “neighbors” networks. The analyzed data were collected from Facebook and afterwards we applied SNA techniques in order to draw some conclusions.